Smaller change in psychological readiness to return to sport is associated with second anterior cruciate ligament injury among younger patients - McPherson, A. L.; Feller, J. A.; Hewett, T. E.; Webster, K. E. (The American Journal of Sports Medicine, 2019)
Background: Lower psychological readiness to return to sport has been reported for younger patients (=20 years) who go on to a second anterior cruciate ligament (ACL) injury. However, changes in psychological readiness and specific psychological responses associated with second injury have not been identified. Purpose/Hypothesis: To identify changes in psychological readiness over time associated with a second ACL injury. It was hypothesized that younger patients who suffered a second injury would have smaller changes in psychological readiness to return to sport when compared with those who did not have a second injury. Study Design: Case-control study; Level of evidence, 2. Methods: Patients =20 years old at the time of surgery who had a primary ACL reconstruction procedure between June 2014 and June 2016 were recruited for this study. The short version of the Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI) scale was completed by patients before their ACL reconstruction and repeated at 12 months after surgery to assess psychological readiness to return to sport. The primary outcome of interest was the relationship between the change in psychological readiness and second ACL injuries. Results: Among 115 young patients who returned to sport after ACL reconstruction, 21 (18%) experienced a second ACL injury. Injured patients did not show improvement in their ACL-RSI score between the preoperative assessment and 12-month time point (58.5 vs 60.8 points, P = .60) and had a significantly smaller change when compared with noninjured patients (9.2 vs 24.9 points, P = .01). When compared with the noninjured group, the injured group reported they were more nervous about playing sport, less confident in playing sport without concern for the knee, more frustrated with having to consider the knee with respect to sport, and more fearful of reinjuring the knee by playing sport (P= .05). Conclusion: Injured patients exhibited less improvement in psychological readiness at a group level and reported different psychological characteristics with regard to return to sport at 12 months after ACL reconstruction as monitored by the ACL-RSI scale.